The Impact of The Tejan of Book on the Kings of Wahb Ibn Munabbih (34-114 A.H.) In History Books "Ibn Ishaq as a model" - Keadan, Rasmeyah Yousif (Journal of Arabic Language Sciences and Literature, 2022)
This study dealt with the impact The Tejan of Book in the history books, and it aimed to clarify the meaning of the concept of The Tejan of Book and its content, and to clarify the issue of doubt in its lineage, and to clarify the extent of the impact of Wahb bin Munabbih’s narrations in The Tejan of Book on the sources and writing of history, and to clarify the extent of the impact of Wahb bin Munabbih’s narrations on the writings of Ibn Ishaq in the books of Biography and Maghazi, and the research relied on the documentary method in tracking events and narratives, and the descriptive analytical method in order to describe and analyze the phenomenon. And the legends, and the crowns reviewed the history of Yemen for a long period of time that extended from the beginning of God’s creation of water and air, until the period of the rule of Saif bin Dhi Yazan as the first crowned king, in addition to the influence of many researchers and historians on Wahb bin Munabbih, perhaps the most important of them is Ibn Ishaq, the author of the most famous books The notation, which is the book of Sir and Maghazi, and was influenced by Ibn Munabbih’s narratives through his narration of the attributable and non-corroborated events, including what was mentioned in the Israelites and books of the Torah and the Gospel that were narrated by Wahb bin Munabbih in the Book of Tijans, in addition It refers to the narratives that were transmitted orally by the Arabs and recorded in the crowns.